Effect of Non-Alcoholic Beer on Older Adults Homocysteine Levels - Cunha, Nathalie (2012)
Objective: To evaluate the effectiveness of non-alcoholic beer (NAB) and non alcoholic beer with a high content of folicacid (NAB-FA) in reducing hyperhomocysteinemia amongst older adults. Design: Quasi-experimental study. Setting: Care homesfor older adults. Participants: Forty older adults aged 72 to 96 years (mean=83), with high serum homocysteine (Hcy) levels,>11μmol/L in women and >12μmol/L in men. Intervention: Those who reported liking NAB were randomly assigned to drinking500 ml/day of NAB (n=8) or NAB-FA (43.7μg of folic acid/100 mL) (n=9). Those who reported not liking NAB were allocated to thecontrol group (n=23), 500ml/day of water. Measurements: Serum levels of Hcy, folic acid and cobalamin evaluated at baseline andafter the intervention. Results: A higher reduction in Hcy levels was observer after beer (NAB and NAB FA) than after wateringestion (3.2μmol/L, interquartile range (IQR)=3.2μmol/L, p<0.001 compared with 0.9μmol/L, IQR=1.5μmol/L, p<0.001).Compared to the water ingestion, this reduction in Hcy levels was higher after NAB FA intake (3.55μmol/L, IQR=2.1μmol/L,p=0.011) than after NAB (2.45μmol/L, IQR=6.3μmol/L; p=0.132). Conclusion: Three week intake of non-alcoholic beer significantlydecreased Hcy levels in older adults with advanced age. When folic acid was integrated into NAB, a considerably lower dose offolic acid was necessary in order to reduce Hcy plasma levels than previously described for that purpose.